2022
DOI: 10.1002/adfm.202208392
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Deposited Pure α‐FAPbI3 Perovskite Solar Cell via Moisture‐Induced Phase Transition Strategy

Abstract: To fabricate stable neat FAPbI3 perovskite with a pure α‐phase (pure α‐FAPbI3) is important in the field of photovoltaic commercialization because of its better bandgap than its alloying counterpart with cesium (Cs) or methylammonium (MA) cations. In this study, the first vapor deposited pure α‐FAPbI3 thin film solar cell with a power conversion efficiency (PCE) over 20% is achieved by regulating the phase transition process. It is found that under high humidity conditions, a fast phase transition between high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…At room temperature, the desired perovskite α-phase is only metastable and easily deteriorates into a thermodynamically favorable, yellow, nonperovskite 2H (δ)-phase that is not particularly photoactive . Early work demonstrated that partial substitution of FA with Cs with as little as 5% is sufficient to eliminate traces of δ-phase presence in XRD patterns, , but such a degree of A-site alloying shifts the band gap to higher energies and has been shown to introduce undesirable compositional inhomogeneities. , Recently, a plethora of fabrication methods and optimization approaches have therefore been developed to attain and stabilize the “unalloyed” perovskite α-phase of FAPbI 3 . ,,,, These alterations to earlier fabrication methods vary from introducing pre- and postannealing steps and additive treatments , to more elaborate stoichiometric engineering techniques, ,, vapor codeposition, and more recently templating and sequential deposition strategies via solution or vapor deposition routes, yielding significant advances in stability and performance.…”
mentioning
confidence: 99%
“…At room temperature, the desired perovskite α-phase is only metastable and easily deteriorates into a thermodynamically favorable, yellow, nonperovskite 2H (δ)-phase that is not particularly photoactive . Early work demonstrated that partial substitution of FA with Cs with as little as 5% is sufficient to eliminate traces of δ-phase presence in XRD patterns, , but such a degree of A-site alloying shifts the band gap to higher energies and has been shown to introduce undesirable compositional inhomogeneities. , Recently, a plethora of fabrication methods and optimization approaches have therefore been developed to attain and stabilize the “unalloyed” perovskite α-phase of FAPbI 3 . ,,,, These alterations to earlier fabrication methods vary from introducing pre- and postannealing steps and additive treatments , to more elaborate stoichiometric engineering techniques, ,, vapor codeposition, and more recently templating and sequential deposition strategies via solution or vapor deposition routes, yielding significant advances in stability and performance.…”
mentioning
confidence: 99%
“…The decreased RMS value further confirms the enhanced quality of perovskite film with adding optimized amount of 502 adhesive. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…The decreased RMS value further confirms the enhanced quality of perovskite film with adding optimized amount of 502 adhesive. [33] To investigate the effect of 502 adhesive on photovoltaic performance, the PSCs with planar structure of FTO/SnO 2 / Perovskite/Spiro-OMeTAD/Ag were prepared (Figure 3a). We tuned the concentration of 502 adhesive in perovskite films to optimize the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, it is difficult to monitor the evaporation rate of multiple precursors with a single QCM, making it unable to identify the individual evaporation rate of precursors, leaving a negative influence on reproducibility [26] . Lastly, it is reported that a small amount of the ammonium salt may remain in the chamber after evaporation, which may re-evaporate during the next evaporation process [30] . Such remnant precursors can affect the composition of the evaporated perovskite, reducing the batch-to-batch reproducibility of evaporated PSCs.…”
Section: Coevaporation Methodsmentioning
confidence: 99%